The Effects of Changing the Effective Crest Length of Labyrinth Side Weir on Discharge Capacity - Dogan, Yusuf; Kaya, Nihat (Springer Heidelberg, 2023)
Labyrinth side weirs have significant advantages according to conventional side weirs in terms of discharge capacity. Labyrinth side weirs are especially advantageous in places where more discharge is required from small weir openings lengths. The most significant feature of labyrinth side weirs is their effective crest length, which enables them to discharge more flow. In this study, the situation where the discharge capacity is decreased due to the narrowing of the crest length of the labyrinth side weir for any reason was experimentally investigated in detail. It was also considered that the potential narrowing could be in the upstream weir crest length. The overflow from the remaining length of the crest was enabled by the 1/3, 2/3, and 3/3 closure of the upstream crest length of the labyrinth side weir. Therefore, it was attempted to determine the decrease in discharge capacity due to the narrowing in the effective crest length. The values of the discharge coefficient were obtained by using the De Marchi approach. The study was conducted for subcritical flow regimes and steady-state flow conditions. A total of 980 experimental runs were conducted in this study. As the length of upstream effective crest length of the triangular labyrinth side weir at the straight channel decreases, the discharge coefficient also decreases. By narrowing the length of effective upstream crest length in 1/3, 2/3, and 3/3 ratios, the total discharge capacity decreased by approximately 10%, 23%, and 48%, respectively.
Keywords: Labyrinth side weir; Crest length; Discharge coefficient; Discharge capacity